Experimental and Simulation Research of AC Ripple Losses in a High Temperature Superconductor Tape - Hongwei Liu; Guosheng Song; Chuanhui Zhang; Jinwen Tan; Wengang Feng (Advances in Condensed Matter Physics)
Current leads in superconducting magnets are widely adopted for heavy current transmission, and HTS DC cables have great advantages when used as current leads for such purposes. However, as an important parameter of HTS DC cables, AC loss has a strong impact on the stability and operation cost of current leads. In this paper, experiments were conducted to measure AC ripple losses of HTS tapes and HTS cables, and simulations of HTS tapes were carried out. The paper has reached conclusions on the relation between AC losses and power frequencies.